New 2, 3-diphenylquinoxaline containing organic D-A-π-A dyes with nickel oxide photocathode prepared by surfactant-mediated synthesis for high performance p-type dye-sensitized solar cells. (April 2019) - Weldekirstos, Hulugirgesh Degefu; Kuo, Ming-Chung; Li, Sie-Rong; Su, Wei-Lin; Desta, Mekonnen Abebayehu; Wu, Wen-Ti; Kuo, Chun-Hong; Sun, Shih-Sheng
Abstract: Dye-sensitized solar cells (DSSCs) are one of the most promising organic photovoltaics. The optimized efficiency of a tandem cell combined with both n- and p-type DSSCs was theoretically predicted to be 43%. The bottleneck for reaching the optimized performance is limited by the p-type half-cell, particularly the lacking of an appropriate semiconducting material as the photocathode. In this regard, we report the surfactant-mediated synthesis of nickel oxide nanomaterial using a chemical co-precipitation method. The new material was fully characterized by XRD, SEM, XPS, EDS, and BET. The BET result indicates the nickel oxide nanoparticles synthesized with surfactant attain higher surface area than the conventional one. In addition, the new organic dyes with electron-deficient diphenylquinoxaline incorporated within the molecular structure were prepared for p-type dye-sensitized solar cells with the newly prepared NiO as the photocathode. The new organic dyes consist of carboxylic acid as the anchoring group, triphenylamine as the electron donor, 2, 3-diphenylquinoxaline as the auxiliary acceptor moiety, 2-methylenemalononitrile as electron acceptor, connected with thiophene, 3, 4-ethylenedioxythiophene, and 2, 2′-bithiophene as the π-spacer. Sensitizers with mono-anchoring group (EH166, EH122, andEH174 ) performed better than their corresponding double-anchoring sensitizers (EH162, EH126, andEH170 ). Among these, dye EH174 exhibited the best conversion efficiency up to 0.207% with a short-circuit photocurrent density of 4.84 mAcm −2, an open-circuit photovoltage of 137 mV, and a fill factor of 0.312. The current results indicate that the combination of electron-deficient quinoxaline motif with suitable π-linker in a D-A-π-A molecular structure is a promising design of p-type sensitizers for NiO-based p -DSSCs. Graphical abstract: Highlights: A surfactant-mediated synthetic protocol for NiO nanoparticles for the photocathode materials of p-type DSSCs were developed. The NiO prepared by surfactant-mediated synthesis exhibited higher surface area than the one prepared by conventional method. A much better efficiency of the p-type DSSCs was realized with newly developed NiO photocathodes. New organic dyes with a D-A-π-A structural framework were designed for p-type DSSCs with the best performance up to 0.207%.